Immediate Psychological Impact among ENT-HNS doctors during the second wave of COVID-19 havoc in Nepal - KC, Asbina; Shakya Malla, Neeta; Mathema, Luna; Khatri, Bijay (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: The priority after the outbreak of COVID-19 pandemic has been treating cases and counting the number of fatalities. But mental health impact has been neglected, even though evidence show that frontline health care workers are at risk of mental health issues in such situations. This study aimed to determine the status of anxiety among ENT-HNS doctors and the associated factors in Nepal during the second wave of COVID-19 havoc in Nepal. Material and Methods: This is a web-based cross-sectional study carried out from 1st May to 31st May 2021. The study participants: ENT-HNS consultants and residents, were approached for the study through different social media, and data was collected through an app-based self-administered questionnaire. The anxiety level was measured using the GAD-7 scale, and the chi-square test was applied to study the factors associated with anxiety. Results: Among sixty-two participating ENT-HNS doctors, 33.9% already had contracted COVID-19, and 77.4% had mild to severe anxiety. Just below half (45.2%) of the participants worked in COVID-dedicated hospitals and treated patients every working day. None of the respondents could comply with social distance at their workplace, and 75.8% believed they lacked sufficient personal protection equipment (PPE). The potential aerosol-generating procedures like epistaxis management, tracheostomy, and flexible endoscopy were regarded as the highest risk of viral transmission by 35.5%, 30.6%, and 21.0% of respondents, respectively. The young doctors, female doctors, and residents were more likely to be anxious than their counterparts. The ENT-HNS doctors who had lost a family member, close relatives, or colleague were seven times more likely to have anxiety. Conclusion: The ENT-HNS doctors are neither immune to the COVID-19 infection nor the anxiety. They must have access to required PPE as well as psychosocial support to prevent anxiety. Early identification and timely intervention at the institutional level are vital to maintaining a well-staffed workforce during a pandemic like COVID-19.